Battery cell, battery device, electric device
Patent Information
- Application Number
- CN202510479529.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-16
- Publication Date
- 2026-10-23
Smart Images

Figure CN122968376A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and more specifically, to a battery cell, a battery device, and an electrical appliance. Background Technology
[0002] With increasing environmental pollution, the new energy industry is attracting more and more attention. Within the new energy industry, battery technology is a crucial factor in its development.
[0003] The development of battery technology requires consideration of various design factors, such as energy density, cycle life, lifespan, capacity, fast charging performance, and reliability. How to provide a battery cell with high energy density, fast charging performance, and high reliability is a pressing technical problem that needs to be solved. Summary of the Invention
[0004] This application is made in view of the above-mentioned issues, and its purpose is to provide a battery cell with high energy density, fast charging performance and high reliability.
[0005] To achieve the above objectives, this application provides a battery cell, a battery device, and an electrical appliance.
[0006] In a first aspect, a battery cell is provided, comprising: a positive electrode sheet, the positive electrode sheet including a positive current collector and a positive electrode film layer disposed on at least one side surface of the positive current collector, the positive electrode film layer including a positive electrode active material, the positive electrode active material including a lithium phosphate; and a negative electrode sheet, the negative electrode sheet including a negative current collector and a negative electrode film layer disposed on at least one side surface of the negative current collector, the negative electrode film layer including a negative electrode active material, the negative electrode active material including a silicon-based material, the one-sided surface density of the negative electrode film layer being 100 mg / 1540.25 mm². 2 Up to 200mg / 1540.25mm 2 A separator membrane is disposed between the positive electrode and the negative electrode. The air permeability G of the separator membrane satisfies: 75s ≤ G ≤ 210s, wherein the air permeability is defined as 100 mL of air passing through 6.45 cm under a pressure of 1.21 kPa. 2 The time taken for the isolation membrane to be in place.
[0007] In this embodiment, the battery cell includes a positive electrode, a negative electrode, and a separator for disposing on the positive and negative electrodes. The positive active material in the positive electrode includes lithium phosphate, and the negative active material in the negative electrode includes silicon-based material. Furthermore, the one-sided surface area density of the negative electrode film is 100 mg / 1540.25 mm². 2 Up to 200mg / 1540.25mm 2Thus, the combination of lithium phosphate and silicon-based materials is beneficial for improving the energy density of individual battery cells; by setting the unilateral density of the negative electrode film within the aforementioned range, the fast-charging performance of the individual battery cells is improved. In the above battery system, during the charging process of the individual battery cells, due to the higher specific capacity of silicon-based materials, more lithium can be inserted into the silicon. However, the extent of lithium insertion is limited by the lithium-ion transport rate in the separator. The lithium-ion transport rate in the separator is related to the separator's permeability, which reflects the resistance to lithium-ion transport. When the separator's permeability is less than or equal to 210s, the resistance to lithium-ion transport is low, which is beneficial for improving the lithium-ion transport rate and thus improving the fast-charging performance of the individual battery cells. When the separator's permeability is greater than or equal to 75s, the separator has higher tensile strength, which can reduce the risk of short circuits between the positive and negative electrodes and thermal runaway of the individual battery cells caused by separator rupture, thus improving the reliability of the individual battery cells.
[0008] In some embodiments, 132s ≤ G ≤ 180s. This results in lower resistance to lithium-ion transport within the separator, which helps to further improve the transport speed of lithium-ions within the separator, leading to better fast-charging performance of the battery cells; simultaneously, the separator has high tensile strength, resulting in higher reliability of the battery cells.
[0009] In some embodiments, the silicon content in the silicon-based material is from 0.3 wt% to 10 wt% based on the total mass of the negative electrode film.
[0010] When the mass content of silicon in the silicon-based material is greater than or equal to 0.3 wt% based on the total mass of the negative electrode film, the battery cell has a high energy density; when the mass content of silicon in the silicon-based material is less than or equal to 10 wt% based on the total mass of the negative electrode film, the combination of the separator and the silicon-based material is beneficial to improving the energy density and fast charging performance of the battery cell.
[0011] In some embodiments, the one-sided density of the negative electrode film is 100 mg / 1540.25 mm². 2 Up to 180mg / 1540.25mm 2 In this way, the negative electrode film has a suitable areal density, which is beneficial for balancing the energy density and fast charging performance of the battery cell.
[0012] In some embodiments, the separator includes a base membrane and coatings disposed on both sides of the base membrane, wherein the porosity of the base membrane is 30% to 60%.
[0013] When the porosity of the base film is greater than or equal to 30%, it facilitates electrolyte wetting and lithium-ion transport, thereby improving the fast-charging performance of the battery cell. When the porosity of the base film is less than or equal to 60%, the separator has higher tensile strength, and the risk of short circuit between the positive and negative electrodes due to separator rupture is lower, which helps improve the reliability of the battery cell. In addition, when the porosity of the base film is between 30% and 60%, the air permeability of the separator can be in the range of 75s to 210s.
[0014] In some embodiments, the porosity of the base film is 35% to 45%. This provides good wettability of the electrolyte to the separator, which is beneficial for improving the lithium-ion transport rate. Simultaneously, the separator also has high tensile strength, reducing the risk of it being punctured by lithium dendrites or breaking under stress. Therefore, the battery cell can possess both good fast-charging performance and high reliability.
[0015] In some embodiments, the base film includes pores, and the pores satisfy at least one of the following conditions:
[0016] The average pore diameter is 10 nm to 400 nm;
[0017] The ratio of the area of the pore to the area of the base film is 10% to 50%.
[0018] In the above embodiments, when the ratio of the average pore diameter or the pore area to the area of the base film meets the above range, the base film has a suitable porosity, which facilitates the electrolyte to wet the separator, is beneficial to the transport of lithium ions, and the battery cell has good fast charging performance.
[0019] In some embodiments, the hole satisfies at least one of the following conditions:
[0020] The average pore diameter is 40 nm to 160 nm;
[0021] The ratio of the area of the pore to the area of the base film is 15% to 30%.
[0022] In the above embodiments, when the ratio of the average pore diameter or the pore area to the area of the base film meets the above range, the base film has a suitable porosity, which facilitates the electrolyte to wet the separator, is beneficial to the transport of lithium ions, and the battery cell has good fast charging performance.
[0023] In some embodiments, the base film satisfies at least one of the following conditions:
[0024] The thickness of the base film is 3.5 μm to 7 μm;
[0025] The areal density of the base film is 2 g / m³. 2 Up to 5g / m2 .
[0026] When the thickness of the base film is greater than or equal to 3.5 μm, the separator has high strength, and the risk of short circuit caused by the positive and negative electrodes due to the separator being punctured is low. When the thickness of the base film is less than or equal to 7 μm, it is beneficial to reduce the space occupied by the separator, thereby improving the energy density of the battery cell.
[0027] The areal density of the base film is greater than or equal to 2 g / m³. 2 In this case, the separator has high strength, and the risk of a short circuit caused by the positive and negative electrodes overlapping due to a puncture in the separator is low; when the areal density of the base film is less than or equal to 5 g / m³. 2 In this case, the base film has a high porosity, which is beneficial to improving the transport speed of lithium ions in the separator, thereby improving the fast charging performance of the battery cell.
[0028] In some embodiments, the coating includes two first functional layers and at least one second functional layer, the first functional layers being disposed on both sides of the base film, and the second functional layer being disposed between the base film and the first functional layer; the first functional layer includes a first inorganic material and a fluoropolymer, and the second functional layer includes a second inorganic material.
[0029] The first and second inorganic materials can improve the wettability and heat resistance of the first and second functional layers to the electrolyte, thereby further improving the fast-charging performance, cycle stability and reliability of the battery cells. The fluoropolymer can improve the processing performance and stability of the separator, reduce the risk of short circuits in the battery cells caused by the movement of the separator in the battery cells, thereby further improving the cycle stability and reliability of the battery cells.
[0030] In some embodiments, the coating comprises two first functional layers and one second functional layer, wherein the second functional layer is disposed between the base film and the first functional layer facing the positive electrode, or between the base film and the first functional layer facing the negative electrode. This provides the separator with better air permeability, which is beneficial for improving the fast-charging performance of the battery cell; furthermore, the second functional layer being disposed between the base film and the first functional layer facing the positive electrode improves the reliability of the battery cell; and the second functional layer being disposed between the base film and the first functional layer facing the negative electrode improves the wettability of the electrolyte to the separator or the negative electrode, facilitating lithium-ion transport, thereby improving the fast-charging performance of the battery cell.
[0031] In some embodiments, the coating comprises two first functional layers and two second functional layers, with the second functional layers disposed between the base film and the first functional layers. This results in a separator with higher mechanical strength, which is beneficial for further improving the reliability of the battery cell; furthermore, the separator also has suitable air permeability, which is beneficial for improving the fast-charging performance of the battery cell.
[0032] In some embodiments, the thickness of the second functional layer is 0.5 μm to 3 μm.
[0033] When the thickness of the second functional layer is greater than or equal to 0.5 μm, it is beneficial to improve the voltage breakdown resistance of the separator and reduce the risk of short circuit between the positive and negative electrodes caused by voltage breakdown of the separator, thereby improving the reliability of the battery cell. When the thickness of the second functional layer is less than or equal to 3 μm, the separator has high air permeability, which is beneficial to improve the lithium ion transport speed, thereby improving the fast charging performance of the battery cell. In addition, when the thickness of the second functional layer is less than or equal to 3 μm, it is also beneficial to reduce the space occupied by the separator and increase the energy density of the battery cell.
[0034] In some embodiments, the thickness of the second functional layer is 0.75 μm to 2 μm. This results in a battery cell with good fast-charging performance, high reliability, and high energy density.
[0035] In some embodiments, the first inorganic material includes one or more of silicon oxide, aluminum oxide, boehmite, barium sulfate, calcium fluoride, calcium oxide, titanium oxide, zinc oxide, magnesium oxide, zirconium oxide, and tin oxide; and / or, the second inorganic material includes one or more of silicon oxide, aluminum oxide, boehmite, barium sulfate, calcium fluoride, calcium oxide, titanium oxide, zinc oxide, magnesium oxide, zirconium oxide, and tin oxide.
[0036] The first and second inorganic materials mentioned above have good heat resistance and suitable insulation properties, while the separator has good heat resistance and the function of isolating the positive and negative electrodes.
[0037] In some embodiments, the fluoropolymer includes polyvinylidene fluoride.
[0038] The aforementioned fluoropolymers have good adhesion, which helps to improve the adhesion between the separator and the positive and negative electrode sheets, reduce the risk of separator wrinkling, and thus reduce the adverse effects of separator wrinkling on lithium-ion transport. The battery cells have good fast-charging performance.
[0039] In some embodiments, along the width direction of the separator, the amount of heat shrinkage T of the separator at 150°C for 30 minutes satisfies: T≤3%.
[0040] During the fast charging process of a battery cell, the battery cell has a high temperature. By setting the thermal shrinkage of the separator to meet the above range, the risk of short circuit between the positive and negative electrode plates caused by the shrinkage of the separator at high temperature can be reduced, which is beneficial to improving the reliability of the battery cell.
[0041] In some embodiments, 0.1% ≤ T ≤ 2%. This results in a separator with a suitable amount of thermal shrinkage, which is beneficial for improving the reliability of individual battery cells and facilitating the fabrication of the separator.
[0042] In some embodiments, the tensile strength G of the separator along its length satisfies: 2700 kgf / cm². 2 ≤G≤6000Kgf / cm 2 .
[0043] In some embodiments, the negative electrode film layer includes a first negative electrode sub-film layer and a second negative electrode film layer, wherein the first negative electrode sub-film layer is located away from the negative electrode current collector relative to the second negative electrode film layer. This facilitates the insertion and diffusion of lithium ions into the negative electrode film layer, thereby improving the fast-charging performance of the battery cell.
[0044] In some embodiments, the first negative electrode film layer comprises the silicon-based material and composite graphite, and the second negative electrode film layer comprises at least one of composite graphite and natural graphite, and the silicon-based material.
[0045] Compared to composite graphite and natural graphite, silicon-based materials have higher specific capacity. They can accept more lithium ions and have a higher lithium intercalation potential, thus preferentially inserting lithium ions into silicon. Placing silicon-based materials in the first negative electrode film layer, away from the negative electrode current collector, is beneficial for improving the fast-charging performance of individual battery cells; placing silicon-based materials in the second negative electrode film layer, closer to the negative electrode current collector, is beneficial for improving the energy density of individual battery cells.
[0046] In some embodiments, the composite graphite includes a body and a coating layer disposed on at least a portion of the surface of the body, the body comprising artificial graphite and the coating layer comprising amorphous carbon. This facilitates the rapid insertion and diffusion of lithium ions into the composite graphite, resulting in better fast-charging performance of the battery cell.
[0047] In some embodiments, the body comprises a plurality of primary particles of artificial graphite. This facilitates the transport and diffusion of lithium ions within the composite graphite, resulting in better fast-charging performance for the battery cell.
[0048] In some embodiments, based on the total mass of the composite graphite, the mass content of amorphous carbon in the coating layer is 2 wt% to 5 wt%. This is beneficial for improving the fast-charging performance of the battery cell and reducing side reactions between the composite graphite and the electrolyte, allowing the battery cell to achieve both good fast-charging performance and long cycle life.
[0049] In some embodiments, the volume average particle size of the negative electrode active material in the first negative electrode film layer is 7.5 μm to 18.5 μm, and the volume average particle size of the negative electrode active material in the second negative electrode film layer is 10.5 μm to 19.5 μm.
[0050] Small-particle-size anode active materials have a higher lithium intercalation speed compared to large-particle-size anode active materials. The above configuration helps to improve the fast-charging performance of battery cells.
[0051] In some embodiments, the thickness ratio of the first negative electrode film layer to the second negative electrode film layer is 2:8 to 8:2. This is beneficial for balancing the fast-charging performance and energy density of the battery cell.
[0052] In some embodiments, the thickness ratio of the first negative electrode film layer to the second negative electrode film layer is 4:6 to 5:5. This is beneficial for improving the fast charging performance of the battery cell.
[0053] In some embodiments, the negative electrode sheet includes a negative electrode conductive layer disposed between the negative electrode current collector and the negative electrode film layer, and the negative electrode conductive layer includes a conductive agent. This improves the conductivity of the negative electrode sheet, thereby enhancing the fast-charging performance of the battery cell.
[0054] In some embodiments, the thickness of the negative electrode conductive layer is 0.5 μm to 2 μm. This is beneficial for balancing the conductivity and thickness of the negative electrode sheet, resulting in a battery cell with good fast-charging performance and high energy density.
[0055] In some embodiments, the lithium-containing phosphate includes a lithium-containing phosphate matrix and a coating layer, the coating layer being located on at least a portion of the surface of the lithium-containing phosphate matrix, and the coating layer comprising carbon elements. This helps to improve the conductivity of the lithium-containing phosphate, facilitating the utilization of the battery cell's capacity and enhancing fast-charging performance.
[0056] In some embodiments, the carbon content is 0.8% to 2.3% by mass based on the total mass of the lithium phosphate. This gives the lithium phosphate good conductivity, facilitating the utilization of the battery cell's capacity and improving fast-charging performance.
[0057] In some embodiments, the positive electrode further includes a positive conductive layer disposed between the positive current collector and the positive electrode film layer, and the positive conductive layer includes a conductive agent. This improves the conductivity of the positive electrode, thereby enhancing the fast-charging performance of the battery cell.
[0058] In some embodiments, the thickness of the positive electrode conductive layer is 0.5 μm to 2 μm. This is beneficial for balancing the conductivity and thickness of the positive electrode sheet, resulting in a battery cell with good fast-charging performance and high energy density.
[0059] In some embodiments, the battery cell includes an electrolyte, which comprises a carboxylic acid ester solvent. Electrolytes comprising carboxylic acid ester solvents have high ionic conductivity and low viscosity, which is beneficial for lithium-ion transport, thereby improving the fast-charging performance of the battery cell.
[0060] In some embodiments, the carboxylic acid ester solvent includes one or more of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, methyl butyrate, and ethyl butyrate.
[0061] In some embodiments, the battery cell includes an electrolyte, which includes an electrolyte salt, including lithium difluorosulfonylimide and lithium hexafluorophosphate.
[0062] Lithium bis(fluorosulfonyl)imide is beneficial for increasing the lithium-ion transference number in the electrolyte, and the combination of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate is beneficial for improving the fast-charging performance of battery cells.
[0063] In some embodiments, the molar concentration of lithium bisfluorosulfonylimide in the electrolyte is from 0.2 mol / L to 0.5 mol / L. This provides a suitable molar concentration of lithium bisfluorosulfonylimide and allows the battery cell to exhibit suitable fast-charging performance.
[0064] In some embodiments, the battery cell includes an electrolyte, which includes additives, including at least one selected from vinylene carbonate, fluoroethylene carbonate, 1,3-propylene sulfonate lactone, vinyl sulfite, and lithium difluorophosphate. In battery cells comprising silicon-based materials, the expansion of the silicon-based materials can significantly damage the SEI film. The aforementioned additives are beneficial for forming a more stable SEI film at the negative electrode, thereby improving the cycle life of the battery cell.
[0065] In some embodiments, the electrolyte injection volume in the battery cell is between 2.2 g / Ah and 2.8 g / Ah. This provides a suitable electrolyte injection volume, resulting in good wettability of the separator, which is beneficial for lithium-ion transport and thus improves the fast-charging performance of the battery cell.
[0066] In some embodiments, the volumetric energy density of the battery cell is between 440 Wh / L and 550 Wh / L, and the charging time from 10% SOC to 80% SOC is between 7 min and 20 min. This achieves a balance between high energy density and good fast-charging performance.
[0067] In a second aspect, a battery device is provided, comprising the battery cell of the first aspect and any of the embodiments thereof.
[0068] Thirdly, an electrical device is provided, comprising a battery cell of the first aspect and any of the embodiments thereof, or a battery device of the second aspect, wherein the battery cell or battery device is used to store or provide electrical energy. Attached Figure Description
[0069] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.
[0070] Figure 1 This is a schematic diagram of a separator membrane according to an embodiment of this application;
[0071] Figure 2 This is a schematic diagram of a separator membrane according to an embodiment of this application;
[0072] Figure 3 This is a schematic diagram of the negative electrode sheet according to an embodiment of this application;
[0073] Figure 4 This is a schematic diagram of the negative electrode sheet according to an embodiment of this application;
[0074] Figure 5 This is a schematic diagram of the positive electrode sheet according to an embodiment of this application;
[0075] Figure 6 This is a schematic diagram of a battery cell according to an embodiment of this application;
[0076] Figure 7 This is a schematic diagram of a battery device according to an embodiment of this application;
[0077] Figure 8 This is a schematic diagram of a vehicle according to an embodiment of this application. Detailed Implementation
[0078] Embodiments of the battery cell, battery device, and electrical appliance of this application have been described in detail with appropriate reference to the accompanying drawings; however, unnecessary details may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0079] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0080] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined with each other to form new technical solutions.
[0081] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0082] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0083] With the continuous expansion of lithium-ion battery applications, higher requirements are being placed on their energy density and fast-charging performance. To improve battery energy density, the areal density of the negative electrode film is generally increased. However, as the areal density of the negative electrode film increases, the migration path of lithium ions becomes longer, resulting in higher internal resistance and affecting the battery's fast-charging performance. Simply adjusting the areal density of the negative electrode film is insufficient to achieve a balance between energy density and fast-charging performance in a single battery cell. In view of the above problems, this application rationally designs the battery cell system to achieve a balance between energy density and fast-charging performance. Specifically, by rationally combining the areal density of the negative electrode film, the negative electrode active materials (including silicon-based materials), and the porosity of the separator, energy density is improved while maintaining fast-charging performance.
[0084] [Battery cell]
[0085] This application provides a battery cell, comprising: a positive electrode sheet, which includes a positive current collector and a positive electrode film layer disposed on at least one side surface of the positive current collector, the positive electrode film layer including a positive active material, the positive active material including a lithium phosphate; and a negative electrode sheet, which includes a negative current collector and a negative electrode film layer disposed on at least one side surface of the negative current collector, the negative electrode film layer including a negative active material, the negative active material including a silicon-based material, and the one-sided surface density of the negative electrode film layer being 100 mg / 1540.25 mm². 2 Up to 200mg / 1540.25mm 2 A separator membrane is placed between the positive and negative electrode plates. The air permeability G of the separator membrane satisfies the following condition: 75s ≤ G ≤ 210s, where the air permeability is the permeability of 100 mL of air passing through 6.45 cm under a pressure of 1.21 kPa. 2 The time required for the isolation membrane to be in place.
[0086] In this embodiment, the density of the negative electrode film layer on one side is 100 mg / 1540.25 mm. 2 Up to 200mg / 1540.25mm 2 For example, the areal density of one side of the negative electrode film can be 100 mg / 1540.25 mm². 2 120mg / 1540.25mm 2 130mg / 1540.25mm 2 150mg / 1540.25mm 2 160mg / 1540.25mm 2 170mg / 1540.25mm 2 180mg / 1540.25mm 2 185mg / 1540.25mm 2190mg / 1540.25mm 2 195mg / 1540.25mm 2 200mg / 1540.25mm 2 Or any value within the above range.
[0087] In this embodiment, the unilateral density of the negative electrode film layer of the battery cell can be detected by the following method: For example, take a single-sided coated negative electrode sheet (if it is a double-sided coated sheet, the negative electrode film layer on one side can be wiped off first), cut it into a small circular piece with an area of S1, weigh it, record its weight as M1, and measure its thickness H1. Then wipe off the negative electrode film layer of the weighed negative electrode sheet, weigh the negative current collector, record its weight as M0, and measure its thickness H0. The unilateral density of the negative electrode film layer = (weight of the negative electrode sheet M1 - weight of the negative current collector M0) / S1.
[0088] In some embodiments, a separator is disposed between the positive and negative electrode plates, and the air permeability G of the separator satisfies: 75s ≤ G ≤ 210s, wherein the air permeability is such that 100 mL of air passes through 6.45 cm under a pressure of 1.21 kPa. 2 The time required for the isolation membrane to be in place.
[0089] The separator can be used to separate the positive and negative electrodes to achieve electrical insulation between them. The air permeability of the separator can be 75s, 78s, 80s, 85s, 90s, 95s, 100s, 105s, 110s, 115s, 120s, 125s, 130s, 132s, 135s, 140s, 145s, 150s, 155s, 160s, 165s, 168s, 170s, 172s, 175s, 178s, 180s, 185s, 190s, 200s, 205s, 210s, or any value within the above range.
[0090] In this embodiment, the air permeability of the separator membrane can be tested using the following method. As an example, the dried separator membrane is cut into 6.45cm pieces. 2 The size was measured by testing 100 mL of air passing through 6.45 cm under a pressure of 1.21 kPa. 2 The time taken for the isolation membrane to be in place is used as the air permeability of the isolation membrane.
[0091] As an example, before sampling the separator, the battery cell is discharged to 2.0V at 1 / 3C, then the battery cell is disassembled, and the separator that is not bonded or only minimally bonded to the negative electrode is taken as a sample. As an example, the separator in the corner area of the innermost or outermost ring of the electrode assembly is taken as a sample for testing.
[0092] The separator membrane may include a base membrane and a coating disposed on at least one side of the base membrane. The air permeability of the separator membrane is related to parameters such as the thickness of the base membrane, the material of the base membrane, the thickness of the separator membrane, the thickness of the coating, the materials in the coating, the particle size of the materials in the coating, and the areal density of the coating. By adjusting these parameters, different air permeabilities of the separator membrane can be achieved. It should be noted that the relationship between the above parameters and the air permeability of the separator membrane is not necessarily linear; changes in the air permeability of the separator membrane can be due to the combined effect of these parameters.
[0093] Because the separator membrane has multiple pores, these interconnected or adjacent pores can form channels for lithium-ion transport. However, these channels are not perfectly straight but have a certain degree of tortuosity. The greater the tortuosity, the greater the resistance to lithium-ion transport. Besides lithium-ions, gases can also be transported through these channels. The permeability of the separator membrane reflects the resistance to lithium-ion passage. In this embodiment, the permeability of the separator membrane is characterized by the time it takes for air to pass through it. The lower the permeability G, the lower the resistance to lithium-ion passage, which is more conducive to lithium-ion transport.
[0094] When the air permeability of the separator is greater than or equal to 75s, the separator has high tensile strength, which can reduce the risk of short circuit between positive and negative electrodes and thermal runaway of battery cells caused by separator rupture, thus improving the reliability of battery cells. When the air permeability of the separator is less than or equal to 210s, the transport resistance of lithium ions in the separator is low, which is conducive to improving the transport speed of lithium ions, thereby improving the fast charging performance of battery cells.
[0095] In this embodiment, the positive electrode active material includes lithium phosphate, the negative electrode active material includes silicon-based material, and the one-sided density of the negative electrode film is 100 mg / 1540.25 mm². 2 Up to 200mg / 1540.25mm 2 This enables battery cells to have relatively high volumetric energy density and fast charging performance.
[0096] Fast charging of silicon-based battery cells can be broadly divided into two stages. In the first stage (e.g., charging a battery cell from 0% SOC to 50% SOC), the silicon-based material has a large number of vacancies, allowing it to accept more lithium ions at high rates. At this stage, the fast charging performance of the battery cell is mainly limited by the transmission speed of lithium ions through the separator. In the second stage (e.g., charging a battery cell from 50% SOC to 100% SOC), since a certain number of lithium ions have already been embedded in the silicon-based material (e.g., after 50% SOC, more than 80% of the vacancies in the silicon-based material are basically filled), the space available for accepting lithium ions in the silicon-based material decreases. Consequently, the number of lithium ions that can be accepted at high rates decreases. Typically, the charging rate of the battery cell is reduced to lower the risk of lithium plating. However, reducing the charging rate at high SOC stages can affect the fast charging performance of the battery and prolong the charging time of the battery cell.
[0097] Therefore, in this embodiment, by controlling the air permeability of the separator to be less than or equal to 210s, the transport resistance of lithium ions in the separator is low, which is beneficial to improving the transport speed of lithium ions. This results in a separator with a higher lithium ion transport speed, which not only improves the fast charging performance in the first stage but also allows for compatibility with silicon-based materials in the second stage, compensating for the impact of the reduced charging rate on fast charging performance. Thus, this embodiment can achieve both high energy density and good fast charging performance. Furthermore, by setting the air permeability of the separator to be greater than or equal to 75s, the tensile strength of the separator is improved, reducing the risk of short circuits and thermal runaway in battery cells caused by separator rupture, thereby improving the reliability of the battery cells.
[0098] In some embodiments, 132s ≤ G ≤ 180s. This results in lower resistance to lithium-ion transport within the separator, which helps to further improve the transport speed of lithium-ions within the separator, leading to better fast-charging performance of the battery cells; simultaneously, the separator has high tensile strength, resulting in higher reliability of the battery cells.
[0099] In some embodiments, the silicon content in the silicon-based material is from 0.3 wt% to 10 wt% based on the total mass of the negative electrode film.
[0100] In embodiments of this application, the silicon-based material may include at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy. Here, elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy can refer to either silicon-based materials or the form in which silicon exists in the negative electrode of the battery after formation. The silicon oxide SiOx, where 0 < x ≤ 2, is used because the bonding mode between silicon atoms and oxygen atoms in the negative electrode film is diverse, and can be SiO, SiO2, etc. 1.2At least one of SiO2 or other possible silicon oxides. Here, silicon-carbon composite can refer to the form in which silicon exists in the negative electrode of a battery after formation. Silicon-carbon composite can also be a silicon-carbon composite formed by certain chemical reactions between silicon and carbon within a single battery cell. It can also be formed by a physical mixture of elemental silicon and elemental carbon, for example, where elemental carbon includes a porous framework, and elemental silicon is located in the pores of the porous framework or on its surface. Silicon-carbon composite can also be formed by coating a carbon layer onto the surface of elemental silicon.
[0101] In addition to silicon-based materials, negative electrode active materials can also include graphite.
[0102] Based on the total mass of the negative electrode film, the mass content of silicon in the silicon-based material can be 0.3wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, or any value within the above range.
[0103] The mass content of silicon in the negative electrode film is a well-known concept in the art and can be detected using well-known equipment and methods. For example, the negative electrode sheet can be immersed in a solvent (e.g., water) to separate the negative electrode active material from the negative electrode current collector. The substances in the negative electrode film can be obtained by filtration and used as a test sample. The silicon content can be obtained by using an ICAP7400 inductively coupled plasma atomic emission spectrometer from ThermoFisher Scientific, USA, in accordance with the GB / T30902-2014 standard.
[0104] When the mass content of silicon in the silicon-based material is greater than or equal to 0.3 wt% based on the total mass of the negative electrode film, the battery cell has a high energy density; when the mass content of silicon in the silicon-based material is less than or equal to 10 wt% based on the total mass of the negative electrode film, the combination of the separator and the silicon-based material is beneficial to improving the energy density and fast charging performance of the battery cell.
[0105] In some embodiments, the density of the negative electrode film layer on one side is 100 mg / 1540.25 mm. 2 Up to 180mg / 1540.25mm 2 In this way, the negative electrode film has a suitable areal density, which is beneficial for balancing the energy density and fast charging performance of the battery cell.
[0106] In some embodiments, when the battery cell is at 100% SOC (State of Charge), the compaction density of the negative electrode film is 1.10 g / cm³. 3 Up to 1.50 g / cm 3 For example, 1.10 g / cm³ 3 1.20g / cm 3 1.25g / cm 3 1.30g / cm 3 1.35g / cm 3 1.4g / cm 3 1.50g / cm 3 Or any value within the above range.
[0107] In addition, it should be noted that when a battery cell is fully charged, the negative electrode film expands, and the compaction density of the negative electrode film will decrease compared to the state of low SOC (e.g., 0% SOC).
[0108] In some embodiments, the separator includes a base membrane and coatings disposed on both sides of the base membrane, wherein the porosity of the base membrane is 30% to 60%.
[0109] The base film can be made of materials such as polyethylene and polypropylene.
[0110] The porosity of the base membrane can be 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 55%, 60%, or any value within the above range.
[0111] The porosity of a base membrane is related to its material. By using different materials, pore sizes, and pore distributions, different porosities can be achieved. The pore distribution can be defined as the ratio of pore area to base membrane area.
[0112] The porosity of the base film can be obtained by methods known to those skilled in the art. For example: After disassembling the battery cell, a separator is obtained. The coating on the separator is scraped off to obtain the base film, and then the porosity of the base film is tested. Specifically: the true density of the base film is measured using Archimedes' method, the weight of the base film is measured using an electronic balance, the thickness of the base film is measured using a micrometer, and the length and width of the base film are measured using a ruler to calculate the volume of the base film. The porosity of the base film = 1 - weight of the base film / (volume of the base film × true density of the base film).
[0113] As an example, the specific procedure for testing the true density of a base film using the Archimedes method is as follows: Weigh the dry base film on a balance to determine its mass in air; immerse the base film in a liquid, ensuring complete submersion and no air bubbles, and record its mass in the liquid; measure the density of the liquid using a standard hydrometer, and then calculate the true density of the base film. The true density of the base film is calculated as follows: True density of the base film = [Mass of the base film in air / (Mass of the base film in air - Mass of the base film in the liquid)] × Density of the liquid.
[0114] The wettability of the electrolyte to the separator is related to the porosity of the base membrane. The greater the porosity of the base membrane, the better the wettability of the electrolyte to the separator, which is more conducive to the transport of lithium ions.
[0115] When the porosity of the base film is greater than or equal to 30%, it facilitates electrolyte wetting and lithium-ion transport, thereby improving the fast-charging performance of the battery cell. When the porosity of the base film is less than or equal to 60%, the separator has higher tensile strength, and the risk of short circuit between the positive and negative electrodes due to separator rupture is lower, which helps improve the reliability of the battery cell. In addition, when the porosity of the base film is between 30% and 60%, the air permeability of the separator can be in the range of 75s to 210s.
[0116] In some embodiments, 35% ≤ P ≤ 45%. This ensures good wettability of the electrolyte to the separator, which is beneficial for improving the lithium-ion transport rate. Simultaneously, the separator also possesses high tensile strength, reducing the risk of it being punctured by lithium dendrites or breaking under stress. Therefore, the battery cell can combine good fast-charging performance with high reliability.
[0117] In some embodiments, the base film includes pores, and the pores satisfy at least one of the following conditions:
[0118] The average pore size ranges from 10 nm to 400 nm;
[0119] The ratio of the area of the pores to the area of the base film is 10% to 50%.
[0120] The average pore size in the base film can be obtained by observing the surface of the base film (perpendicular to the thickness direction) using SEM and statistically analyzing the data. For example, a specific field of view can be used to count the number of pores and the diameter of each pore, and the average of the measured diameters of multiple pores can be taken as the pore size. The pore diameter can be obtained by treating the pore as an equivalent circle and using the diameter of the equivalent circle as the pore diameter.
[0121] The ratio of the area of pores in the base film to the area of the base film can be obtained by observing the surface of the base film (the surface of the base film is perpendicular to the thickness direction of the base film) using SEM and then calculating the ratio. For example, by taking a specific field of view, counting the number of pores and the area of each pore, the ratio of the sum of the areas of multiple pores to the area of the field of view is the ratio of the area of pores in the base film to the area of the base film.
[0122] The average pore size in the base film can be 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 190nm, 200nm, 220nm, 250nm, 280nm, 300nm, 320nm, 350nm, 380nm, 400nm, or any value within the above range.
[0123] The ratio of the area of the pores to the area of the base film can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or any value within the above range.
[0124] The porosity of the base membrane is related to the size of the pores in the base membrane and the ratio of the pore area to the base membrane area. The larger the pores in the base membrane and the larger the ratio of the pore area to the base membrane area, the greater the porosity of the base membrane.
[0125] In the above embodiments, when the size of the pores or the ratio of the pore area to the area of the base film meets the above range, the base film has a suitable porosity, which facilitates the electrolyte to wet the separator, is beneficial to the transport of lithium ions, and the battery cell has good fast charging performance.
[0126] In some embodiments, the hole satisfies at least one of the following conditions:
[0127] The average pore size ranges from 40 nm to 160 nm;
[0128] The ratio of the pore area to the base film area is 15% to 30%.
[0129] In the above embodiments, when the size of the pores or the ratio of the pore area to the area of the base film meets the above range, the base film has a suitable porosity, which facilitates the electrolyte to wet the separator, is beneficial to the transport of lithium ions, and the battery cell has good fast charging performance.
[0130] In some embodiments, the base film satisfies at least one of the following conditions:
[0131] The thickness of the base film is 3.5 μm to 7 μm;
[0132] The areal density of the base film is 2 g / m³. 2 Up to 5g / m 2 .
[0133] The thickness of the base film can be 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm or any value within the above range.
[0134] The thickness of the base film 80 can be represented by d1. The thickness of the base film can be measured as follows: The thickness of the base film is measured at multiple (e.g., 10) locations, and the average value of the multiple thicknesses is taken as d1.
[0135] When the thickness of the base film is greater than or equal to 3.5 μm, the separator has high strength, and the risk of short circuit caused by the positive and negative electrodes due to the separator being punctured is low. When the thickness of the base film is less than or equal to 7 μm, it is beneficial to reduce the space occupied by the separator, thereby improving the energy density of the battery cell.
[0136] The areal density of the base film can be 2 g / m³. 2 2.2g / m 2 2.5g / m 2 2.8g / m 2 3g / m 2 3.2g / m 2 3.5g / m 2 3.8g / m 2 4g / m 2 4.2g / m 2 4.5g / m 2 4.8g / m 2 5g / m 2 Or any value within the above range.
[0137] The areal density of the base film is greater than or equal to 2 g / m³. 2 In this case, the separator has high strength, and the risk of a short circuit caused by the positive and negative electrodes overlapping due to a puncture in the separator is low; when the areal density of the base film is less than or equal to 5 g / m³. 2 In this case, the base film has a high porosity, which is beneficial to improving the transport speed of lithium ions in the separator, thereby improving the fast charging performance of the battery cell.
[0138] Figure 1 This is a schematic diagram of a separator membrane according to an embodiment of this application. In some embodiments, such as... Figure 1As shown, the coating includes two first functional layers 801 and at least one second functional layer 802. The first functional layer 801 is disposed on both sides of the base film, and the second functional layer 802 is disposed between the base film 80 and the first functional layer 801. The first functional layer 801 includes a first inorganic material and a fluoropolymer, and the second functional layer 802 includes a second inorganic material.
[0139] At least one second functional layer 802 may include one second functional layer 802, or it may include two second functional layers 802. As an example, such as... Figure 1 As shown, the coating includes a second functional layer 802.
[0140] The first and second inorganic materials can improve the wettability and heat resistance of the first functional layer 801 and the second functional layer 802 to the electrolyte, thereby further improving the fast charging performance, cycle stability and reliability of the battery cell. The fluoropolymer can improve the processing performance and stability of the separator, reduce the risk of short circuit in the battery cell caused by the movement of the separator in the battery cell, thereby further improving the cycle stability and reliability of the battery cell.
[0141] In some embodiments, the coating includes two first functional layers 801 and one second functional layer 802. The second functional layer 802 is disposed between the base film 80 and the first functional layer 801 facing the positive electrode, or the second functional layer 802 is disposed between the base film 80 and the first functional layer 801 facing the negative electrode. Thus, the separator has good air permeability and high porosity, which is beneficial for improving the fast-charging performance of the battery cell.
[0142] The second functional layer is disposed between the base film and the first functional layer facing the positive electrode, which helps to improve the reliability of the battery cell; the second functional layer is disposed between the base film and the first functional layer facing the negative electrode, which helps to improve the wettability of the electrolyte to the separator or negative electrode, facilitates the transport of lithium ions, and thus helps to improve the fast charging performance of the battery cell.
[0143] Figure 2 This is a schematic diagram of a separator membrane according to an embodiment of this application. In some embodiments, such as Figure 2 As shown, the coating includes two first functional layers 801 and two second functional layers 802, with the second functional layers 802 disposed between the base film 80 and the first functional layers 801. This results in a separator with higher mechanical strength, which is beneficial for further improving the reliability of the battery cell; in addition, the separator also has a suitable porosity, which is beneficial for improving the fast-charging performance of the battery cell.
[0144] In some embodiments, the thickness of the second functional layer 802 is 0.5 μm to 3 μm.
[0145] The thickness of the second functional layer can be 0.5μm, 0.6μm, 0.75μm, 0.8μm, 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, 2.2μm, 2.5μm, 2.8μm, 3μm or any value within the above range.
[0146] The thickness of the second functional layer 802 can be represented by d2. The thickness of the second functional layer can be measured in the following way. For example, after disassembling the battery cell to obtain the separator, the separator is observed using a scanning electron microscope (SEM), and the thickness of the second functional layer at ten different locations is measured. Then, the average of these ten thicknesses is taken as the final thickness of the second functional layer.
[0147] When the thickness of the second functional layer 802 is greater than or equal to 0.5 μm, it is beneficial to improve the voltage breakdown resistance of the separator and reduce the risk of short circuit between the positive and negative electrodes caused by voltage breakdown of the separator, thereby improving the reliability of the battery cell. When the thickness of the second functional layer 802 is less than or equal to 3 μm, the separator has high air permeability, which is beneficial to improve the lithium ion transport speed, thereby improving the fast charging performance of the battery cell. In addition, when the thickness of the second functional layer 802 is less than or equal to 3 μm, it is also beneficial to reduce the space occupied by the separator and increase the energy density of the battery cell.
[0148] In some embodiments, the thickness of the second functional layer 802 is 0.75 μm to 2 μm. This results in a battery cell exhibiting good fast-charging performance, high reliability, and high energy density.
[0149] In some embodiments, the first inorganic material includes one or more of silicon oxide, aluminum oxide, boehmite, barium sulfate, calcium fluoride, calcium oxide, titanium oxide, zinc oxide, magnesium oxide, zirconium oxide, and tin oxide; and / or, the second inorganic material includes one or more of silicon oxide, aluminum oxide, boehmite, barium sulfate, calcium fluoride, calcium oxide, titanium oxide, zinc oxide, magnesium oxide, zirconium oxide, and tin oxide.
[0150] The first and second inorganic materials mentioned above have good heat resistance and suitable insulation properties, while the separator has good heat resistance and the function of isolating the positive and negative electrodes.
[0151] The first inorganic substance and the second inorganic substance can be the same material or different materials. As an example, both the first inorganic substance and the second inorganic substance include aluminum oxide.
[0152] In some embodiments, the fluoropolymer includes polyvinylidene fluoride.
[0153] The aforementioned fluoropolymers have good adhesion, which helps to improve the adhesion between the separator and the positive and negative electrode sheets, reduce the risk of separator wrinkling, and thus reduce the adverse effects of separator wrinkling on lithium-ion transport. The battery cells have good fast-charging performance.
[0154] In some embodiments, the amount of heat shrinkage T of the separator at 150°C for 30 minutes along the width direction of the separator satisfies: T≤3%.
[0155] The heat shrinkage amount T of the separator film can be 3%, 2.8%, 2.5%, 2.2%, 2%, 1.8%, 1.5%, 1.2%, 1%, 0.8%, 0.6%, 0.5%, 0.4%, 0.3%, 0.2%, 0.1%, or any value within the above range.
[0156] The separator has a length direction, a width direction, and a thickness direction. The length direction of the separator can be... Figure 1 In the figure, the x-direction can be the thickness direction of the separator, which can be the y-direction. The width direction of the separator can be a direction perpendicular to both the thickness and length directions.
[0157] During the fast charging process of a battery cell, the battery cell has a high temperature. By setting the thermal shrinkage of the separator to meet the above range, the risk of short circuit between the positive and negative electrode plates caused by the shrinkage of the separator at high temperature can be reduced, which is beneficial to improving the reliability of the battery cell.
[0158] In some embodiments, 0.1% ≤ T ≤ 2%. This results in a separator with a suitable amount of thermal shrinkage, which is beneficial for improving the reliability of individual battery cells and facilitating the fabrication of the separator.
[0159] In some embodiments, the tensile strength G of the separator along its length satisfies: 2700 kgf / cm². 2 ≤G≤6000Kgf / cm 2 .
[0160] The tensile strength G of the separator can be 2700 kgf / cm. 2 3000Kgf / cm 2 3500Kgf / cm 2 3800Kgf / cm 2 4000Kgf / cm 2 4500Kgf / cm 2 4800Kgf / cm 2 5000Kgf / cm 2 5200Kgf / cm 2 5500Kgf / cm 2 5800Kgf / cm2 6000Kgf / cm 2 Or any value within the above range.
[0161] Silicon-based materials have a high expansion rate. During the charge-discharge cycle of a battery cell, the electrode assembly, including those made of silicon-based materials, undergoes significant expansion, and the separator within the electrode assembly is subjected to considerable forces (e.g., tensile forces). By setting the strength of the separator to meet the aforementioned range, the risk of the separator cracking or being punctured by lithium dendrites due to low strength during the charge-discharge cycle of the battery cell can be reduced. This reduces the risk of short circuits in the battery cell and improves its reliability.
[0162] Figure 3 This is a schematic diagram of the negative electrode sheet according to an embodiment of this application. In some embodiments, such as... Figure 3 As shown, the negative electrode film layer 61 includes a first negative electrode sub-film layer 611 and a second negative electrode sub-film layer 612. The first negative electrode sub-film layer 611 is farther away from the negative electrode current collector than the second negative electrode sub-film layer 612. This facilitates the insertion and diffusion of lithium ions in the negative electrode film layer 61, thereby improving the fast charging performance of the battery cell.
[0163] In some embodiments, the first negative electrode film layer 611 comprises silicon-based material and composite graphite, and the second negative electrode film layer 612 comprises composite graphite and / or natural graphite and silicon-based material.
[0164] Compared to composite graphite and natural graphite, silicon-based materials have higher specific capacity. Silicon-based materials can accept more lithium ions and have a higher lithium intercalation potential, thus allowing lithium ions to preferentially intercalate into them. By placing silicon-based material in the first negative electrode film layer 611, which is far from the negative electrode current collector, the fast-charging performance of the battery cell is improved; by placing silicon-based material in the second negative electrode film layer 612, which is close to the negative electrode current collector, the energy density of the battery cell is improved.
[0165] In some embodiments, the first negative electrode film layer 611 comprises a silicon-based material and composite graphite, and the second negative electrode film layer 612 comprises composite graphite and / or natural graphite.
[0166] In some embodiments, the first negative electrode film layer 611 comprises composite graphite, the second negative electrode film layer 612 comprises composite graphite and / or natural graphite, and a silicon-based material.
[0167] In some embodiments, the composite graphite includes a body and a coating layer disposed on at least a portion of the surface of the body. The body includes artificial graphite, and the coating layer includes amorphous carbon. This facilitates the rapid insertion and diffusion of lithium ions into the composite graphite, resulting in better fast-charging performance of the battery cell.
[0168] In some embodiments, the body comprises multiple primary particles of artificial graphite. This facilitates the transport and diffusion of lithium ions within the composite graphite, resulting in better fast-charging performance for the battery cell.
[0169] The bulk consists of multiple primary particles of artificial graphite. In other words, in composite graphite, the morphology of the bulk can be secondary particles formed by the agglomeration of multiple primary particles.
[0170] In some embodiments, the mass content of amorphous carbon in the coating layer is 2 wt% to 5 wt% based on the total mass of the composite graphite.
[0171] Based on the total mass of the composite graphite, the mass content of amorphous carbon in the coating layer can be 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 4.8wt%, 5wt%, or any value within the above range.
[0172] In the above embodiments, the amorphous carbon has a suitable mass content, which is beneficial to improving the fast charging performance of the battery cell and reducing the side reactions between composite graphite and electrolyte. The battery cell can achieve both good fast charging performance and long cycle life.
[0173] In some embodiments, the resistivity of the composite graphite powder is less than or equal to 0.04 Ω·cm. This is beneficial for improving the conductivity of the negative electrode, thereby improving the fast-charging performance of the battery cell.
[0174] The resistivity of composite graphite powder can be 0.04 Ω·cm, 0.035 Ω·cm, 0.03 Ω·cm, 0.025 Ω·cm, 0.02 Ω·cm, 0.01 Ω·cm or any value within the above range.
[0175] In some embodiments, the compacted density of composite graphite powder under 2000 N pressure is 1.5 g / cm³. 3 Up to 1.7 g / cm 3 For example, the compacted density of composite graphite powder under 2000N pressure can be 1.5 g / cm³. 3 1.55g / cm 3 1.6g / cm 3 1.65g / cm 3 1.68g / cm 3 1.7g / cm 3 Or any value within the above range.
[0176] In some embodiments, the charge capacity of the composite graphite at a 0.1C rate is greater than or equal to 360 mAh / g. For example, it can be 360 mAh / g, 362 mAh / g, 365 mAh / g, 368 mAh / g, 370 mAh / g, 380 mAh / g, 385 mAh / g, or any value within the above range.
[0177] The specific charge capacity of the negative electrode active material (e.g., composite graphite) can be measured as follows. For example, the negative electrode sheet is cut to a specific size, then assembled with a lithium sheet to form a coin cell, and the charge capacity of the coin cell is then tested. The specific charge capacity of the negative electrode active material = the charge capacity of the coin cell / the mass of the negative electrode active material.
[0178] In some embodiments, the volume average particle size of the negative electrode active material in the first negative electrode film layer 611 is 7.5 μm to 18.5 μm, and the volume average particle size of the negative electrode active material in the second negative electrode film layer 612 is 10.5 μm to 19.5 μm.
[0179] The volume average particle size of the negative electrode active material in the first negative electrode film layer 611 is the volume average particle size of all the negative electrode active materials mixed together. For example, if the first negative electrode film layer 611 includes silicon-based materials and composite graphite, the volume average particle size of the negative electrode active material in the first negative electrode film layer 611 is the volume average particle size of the mixture of silicon-based materials and composite graphite. Similarly, the volume average particle size of the negative electrode active material in the second negative electrode film layer 612 is the volume average particle size of all the negative electrode active materials mixed together.
[0180] The volume average particle size of the negative electrode active material in the first negative electrode film layer 611 can be 7.5μm, 8μm, 8.5μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 18.5μm or any value within the above range.
[0181] Small-particle-size anode active materials have a higher lithium intercalation speed compared to large-particle-size anode active materials. The above configuration helps to improve the fast-charging performance of battery cells.
[0182] In some embodiments, the thickness ratio of the first negative electrode film layer 611 to the second negative electrode film layer 612 is 2:8 to 8:2. This is beneficial for balancing the fast-charging performance and energy density of the battery cell.
[0183] The thickness ratio of the first negative electrode film layer 611 and the second negative electrode film layer 612 can be 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 or any value within the above range.
[0184] In some embodiments, the thickness ratio of the first negative electrode film layer 611 to the second negative electrode film layer 612 is 4:6 to 5:5. This is beneficial for improving the fast charging performance of the battery cell.
[0185] Figure 4 This is a schematic diagram of the negative electrode sheet according to an embodiment of this application. In some embodiments, such as... Figure 4 As shown, the negative electrode sheet 6 includes a negative electrode conductive layer 62, which is disposed between the negative electrode current collector 60 and the negative electrode film layer 61. The negative electrode conductive layer 62 includes a conductive agent. This improves the conductivity of the negative electrode sheet, thereby improving the fast charging performance of the battery cell.
[0186] Conductive agents include one or more of the following: superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0187] In some embodiments, the thickness of the negative electrode conductive layer 62 is 0.5 μm to 2 μm.
[0188] The thickness of the negative electrode conductive layer 62 can be 0.5μm, 0.8μm, 1μm, 1.2μm, 1.5μm, 1.8μm, 1.9μm, 2μm or any value within the above range.
[0189] The thickness of the negative electrode conductive layer 62 meets the above range, which is beneficial to balance the conductivity and thickness of the negative electrode sheet, and the battery cell has good fast charging performance and high energy density.
[0190] Lithium-containing phosphates can refer to lithium-containing transition metal phosphates with an olivine structure, such as lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, and their modified forms. The modified forms can include at least one of substances obtained through doping modification and substances obtained through coating modification.
[0191] In some embodiments, the lithium phosphate includes a lithium phosphate matrix and a coating layer located on at least a portion of the surface of the lithium phosphate matrix, the coating layer comprising carbon elements. This helps to improve the conductivity of the lithium phosphate, facilitating the utilization of the battery cell's capacity.
[0192] In some embodiments, the carbon content is 0.8% to 2.3% based on the total mass of lithium phosphate.
[0193] Based on the total mass of the lithium phosphate cathode active material, the mass content of carbon can be 0.8%, 1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, or any range of the above values.
[0194] In the above embodiments, lithium phosphate has good conductivity, which facilitates the utilization of the battery cell capacity and the improvement of fast charging performance.
[0195] In some embodiments, the coating layer also includes Li 3-d1 Fe 2-d1 M3 d1 (PO m1 ) n1 The substances are defined as follows: 0≤d1≤1, 3≤m1≤5, 2≤n1≤4; M3 includes one or more of Ti, Zr, Hf, Ge, and Sn.
[0196] In some embodiments, M3 is a +4 price.
[0197] In some embodiments, the general formula of the lithium phosphate matrix is Li x D y Me a1 M b1 P 1-c1 X c1 Y z Compounds wherein 0.5≤x≤1.3, 0≤y≤1.3, and 0.9≤x+y≤1.3; 0.9≤a1≤1.5, 0≤b1≤0.5, and 0.9≤a1+b1≤1.5; 0≤c1≤0.5; 3≤z≤5; D includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of Cl, C, and N; Y includes one or more of O and F.
[0198] In the general formula of lithium phosphate matrix, x can be 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.3 or any of the above values; y can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.3 or any of the above values; a1 can be 0.9, 1, 1.2, 1.3, 1.4, 1.5 or any of the above values; b1 can be 0, 0.1, 0.2, 0.3, 0.4, 0.5 or any of the above values; c1 can be 0, 0.1, 0.2, 0.3, 0.4, 0.5 or any of the above values; and z can be 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5 or any of the above values.
[0199] During the charging and discharging process of a single battery cell, the molar content of lithium, oxygen, and other elements in lithium phosphate varies within a certain range.
[0200] In some embodiments, the lithium phosphate includes at least one of LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4. The aforementioned lithium phosphates exhibit high structural stability, which helps to improve the cycle life of battery cells.
[0201] During the charging and discharging process, lithium (Li) undergoes insertion / extraction and consumption within a single battery cell. The molar content of Li in the positive electrode active material varies depending on the discharge state of the cell. In the examples of positive electrode active materials in this application, the molar content of Li refers to the initial state of the material, i.e., the state before feeding. After charge-discharge cycles, the molar content of Li changes when the positive electrode active material is applied to the battery system. Similarly, the molar content of O in the examples of positive electrode active materials in this application is only an ideal value. Oxygen release from the crystal lattice causes changes in the molar content of O, resulting in fluctuations in the actual molar content of O.
[0202] In some embodiments, the compaction density of the positive electrode active material at 30000N is 2.55 g / cm³. 3 ~2.75g / cm 3 For example, it could be 2.55 g / cm³. 3 2.6g / cm 3 2.65g / cm 3 2.7g / cm 3 2.72 g / cm 3 2.75g / cm 3 Or any value within the above range.
[0203] If the powder compaction density of the positive electrode active material meets the above range, it is beneficial to obtain a positive electrode sheet with a higher compaction density, which in turn helps to improve the energy density of the battery cell.
[0204] In some embodiments, the one-sided density of the positive electrode film is 230 mg / 1540.25 mm². 2 Up to 430mg / 1540.25mm 2 For example, it could be 230mg / 1540.25mm. 2 250mg / 1540.25mm 2 280mg / 1540.25mm 2 300mg / 1540.25mm 2 320mg / 1540.25mm 2 350mg / 1540.25mm 2 380mg / 1540.25mm2 400mg / 1540.25mm 2 430mg / 1540.25mm 2 Or any value within the above range.
[0205] The areal density of one side of the positive electrode film is related to the energy density and fast-charging performance of the battery cell. The greater the areal density of one side of the positive electrode film, the better it is for improving the energy density of the battery cell; the smaller the areal density of one side of the positive electrode film, the better it is for lithium-ion transport and the better it is for improving the fast-charging performance of the battery cell.
[0206] If the areal density of one side of the positive electrode film meets the above range, the battery cell can achieve both high energy density and good fast charging performance.
[0207] In some embodiments, when the battery cell is at 100% SOC (State of Charge), the compaction density of the positive electrode film is 2.65 g / cm³. 3 Up to 2.85 g / cm 3 For example, it is 2.65 g / cm³. 3 2.68g / cm 3 2.7g / cm 3 2.75g / cm 3 2.8g / cm 3 2.85g / cm 3 Or any value within the above range.
[0208] In some embodiments, the thickness of the positive current collector is 10 μm to 15 μm. For example, it can be 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm, 15 μm or any value within the above range.
[0209] The thickness of the positive electrode current collector meets the above range, and the positive electrode current collector occupies a suitable space, which is beneficial to improving the energy density of the battery cell.
[0210] Figure 5 This is a schematic diagram of a positive electrode sheet according to an embodiment of this application. In some embodiments, such as... Figure 5 As shown, the positive electrode 5 includes a positive current collector 50, a positive conductive layer 52, and a positive film layer 51 disposed on at least one side surface of the positive current collector 50. The positive conductive layer 52 is disposed between the positive current collector 50 and the positive film layer 51, and includes a conductive agent. This improves the conductivity of the positive electrode, thereby improving the fast-charging performance of the battery cell.
[0211] In the positive electrode conductive layer, the conductive agent includes one or more of the following: superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0212] In some embodiments, the positive conductive layer further includes an adhesive, which includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polyacrylic acid and fluorinated acrylate resins.
[0213] In some embodiments, the thickness of the positive electrode conductive layer is 0.5 μm to 2 μm. This is beneficial for balancing the conductivity and thickness of the positive electrode sheet, resulting in a battery cell with good fast-charging performance and high energy density.
[0214] In some embodiments, the battery cell includes an electrolyte, which comprises a carboxylic acid ester solvent. Electrolytes comprising carboxylic acid ester solvents have high ionic conductivity and low viscosity, which is beneficial for lithium-ion transport, thereby improving the fast-charging performance of the battery cell.
[0215] As an example, carboxylic acid ester solvents include compounds with the structure shown in Formula I.
[0216]
[0217] R1 and R2 each independently include at least one of C1-C5 alkyl groups and C1-C5 haloalkyl groups.
[0218] In some embodiments, the carboxylic acid ester solvent includes one or more of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, methyl butyrate, and ethyl butyrate.
[0219] In some embodiments, the carboxylic acid ester solvent includes one or more of methyl acetate or ethyl acetate.
[0220] In some embodiments, the battery cell includes an electrolyte, which includes an electrolyte salt, including lithium hexafluorophosphate.
[0221] In some embodiments, the battery cell includes an electrolyte, which includes an electrolyte salt, including lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate.
[0222] Lithium bis(fluorosulfonyl)imide is beneficial for increasing the lithium-ion transference number in the electrolyte, and the combination of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate is beneficial for improving the fast-charging performance of battery cells.
[0223] In some embodiments, the molar concentration of lithium bis(fluorosulfonyl)imide in the electrolyte is from 0.2 mol / L to 0.5 mol / L.
[0224] The molar concentration of lithium bis(fluorosulfonyl)imide can be 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, or any value within the above range.
[0225] In the above embodiments, lithium bis(fluorosulfonyl)imide has a suitable molar concentration, and the battery cells have suitable fast-charging performance.
[0226] In some embodiments, the battery cell includes an electrolyte, which includes additives, including at least one of vinylene carbonate, fluoroethylene carbonate, 1,3-propylene sulfonate lactone, vinyl sulfite, and lithium difluorophosphate.
[0227] In battery cells containing silicon-based materials, the expansion of silicon-based materials can lead to significant damage to the SEI film. The aforementioned additives help to form a more stable SEI film at the negative electrode, which is beneficial to improving the cycle life of the battery cell.
[0228] In some embodiments, the electrolyte injection volume in the battery cell is from 2.2 g / Ah to 2.8 g / Ah.
[0229] The electrolyte injection volume is the ratio of the electrolyte mass to the capacity of the battery cell. The electrolyte injection volume can be 2.2 g / Ah, 2.3 g / Ah, 2.4 g / Ah, 2.5 g / Ah, 2.6 g / Ah, 2.7 g / Ah, 2.75 g / Ah, 2.8 g / Ah, or any value within the above range.
[0230] In the above embodiments, the electrolyte has a suitable injection volume and good wettability to the separator, which is beneficial to the transport of lithium ions and thus helps to improve the fast charging performance of the battery cell.
[0231] In some embodiments, the volumetric energy density of the battery cell is 440Wh / L to 550Wh / L, and the charging time for the battery cell from 10% SOC to 80% SOC is 7 min to 20 min.
[0232] The volumetric energy density of a single battery cell can be 440Wh / L, 450Wh / L, 480Wh / L, 490Wh / L, 500Wh / L, 510Wh / L, 520Wh / L, 530Wh / L, 535Wh / L, 540Wh / L, 550Wh / L, or any value within the above range.
[0233] The charging time for a single battery cell from 10% SOC to 80% SOC can be 7 min, 7.5 min, 8 min, 8.5 min, 9 min, 9.5 min, 10 min, 10.5 min, 11 min, 11.5 min, 12 min, 12.5 min, 13 min, 13.5 min, 14 min, 14.5 min, 15 min, 15.5 min, 16 min, 16.5 min, 17 min, 18 min, 19 min, 19.5 min, 20 min, or any value within the above range.
[0234] Figure 6 This is a schematic diagram of the structure of a battery cell according to an embodiment of this application. In one embodiment of this application, for example, referring to... Figure 6 As shown, the battery cell 3 includes a housing 31, an end cap assembly 32, and an electrode assembly 33. The housing 31 has an opening for accommodating the electrode assembly 33, and the end cap assembly 32 is used to close the opening. The electrode assembly 33 may include a positive electrode, a negative electrode, and a separator between the positive electrode and the negative electrode.
[0235] In some embodiments, the end cap assembly 32 includes electrode terminals 322, such as Figure 6 As shown, the end cap assembly 32 includes two electrode terminals 322, one of which is a positive electrode terminal and the other is a negative electrode terminal.
[0236] The battery cell 3 also includes a connecting member 34 for connecting the tab 331 and the electrode terminal 322 of the electrode assembly 33. For example, one connecting member 34 is used to connect the tab of the positive electrode and the positive electrode terminal, and another connecting member 34 is used to connect the tab of the negative electrode and the negative electrode terminal.
[0237] The electrode assembly 33 can be formed by a positive electrode, a negative electrode, and a separator through a winding or stacking process. As an example, the electrode assembly 33 is formed by a winding process of a positive electrode, a negative electrode, and a separator.
[0238] In this embodiment of the application, the battery cell can be a secondary battery, which refers to a battery cell that can be recharged to activate the active materials and continue to be used after the battery cell has been discharged.
[0239] The battery cell can be a lithium-ion battery.
[0240] Figure 7 A partial structural schematic diagram of the battery device 10 according to an embodiment of this application is shown. For example, as... Figure 7As shown, the battery device 10 of this application embodiment may include a plurality of battery cells 3 to meet different power usage requirements. The shape of the battery cell 3 in this application embodiment can be set according to actual application. For example, the battery cell 3 can be cylindrical, or it can be cuboid or other shapes, and this application embodiment is not limited to this.
[0241] It should be understood that, such as Figure 7 As shown, the battery device 10 of this embodiment may further include a housing 11, which can be used to accommodate multiple battery cells 3. The housing 11 of this embodiment has a hollow interior, and the multiple battery cells 3 are accommodated within the housing 11. The housing 11 may include two parts, referred to herein as a first housing portion 111 and a second housing portion 112, which are fastened together. The shapes of the first housing portion 111 and the second housing portion 112 can be determined according to the shape of the components housed inside, for example, according to the shape of the combination of the multiple battery cells 3 housed inside. At least one of the first housing portion 111 and the second housing portion 112 has an opening. For example, as... Figure 7 As shown, the first housing portion 111 and the second housing portion 112 can both be hollow cuboids with one open side each. The openings of the first housing portion 111 and the second housing portion 112 are opposite to each other, and the first housing portion 111 and the second housing portion 112 are interlocked to form a housing 11 with a closed chamber, which can be used to accommodate multiple battery cells 3. The multiple battery cells 3 are connected in parallel, series, or mixed and placed inside the housing 11 formed by the interlocking of the first housing portion 111 and the second housing portion 112.
[0242] For example, unlike Figure 7 As shown, either the first housing portion 111 or the second housing portion 112 may have only one hollow cuboid with an opening, while the other is plate-shaped to cover the opening. Taking the second housing portion 112 as a hollow cuboid with one opening and the first housing portion 111 as a plate-shaped example, then the first housing portion 111 covers the opening of the second housing portion 112 to form a housing 11 with a closed chamber, which can be used to accommodate multiple battery cells 3.
[0243] The technical solutions described in the embodiments of this application are applicable to various electrical devices that use battery devices.
[0244] Electrical equipment can include vehicles, mobile phones, portable devices, laptops, ships, spacecraft, electric toys, and power tools, etc. Vehicles can be gasoline-powered cars, natural gas-powered cars, or new energy vehicles; new energy vehicles can be pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles, etc. Spacecraft include airplanes, rockets, space shuttles, and spacecraft, etc. Electric toys include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Power tools include metal cutting power tools, grinding power tools, assembly power tools, and railway power tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators, and electric planers, etc. This application does not impose any special limitations on the above-mentioned electrical equipment.
[0245] For ease of explanation, the following embodiments use a vehicle as an example of electrical equipment.
[0246] For example, such as Figure 8 The diagram shown is a structural schematic of a vehicle according to one embodiment of this application. Vehicle 1 can be a gasoline-powered vehicle, a natural gas-powered vehicle, or a new energy vehicle. New energy vehicles can be pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles, etc. A motor 40, a controller 30, and a battery device 10 can be installed inside vehicle 1. The controller 30 controls the battery device 10 to supply power to the motor 40. For example, the battery device 10 can be installed at the bottom, front, or rear of vehicle 1. The battery device 10 can be used to power vehicle 1. For example, the battery device 10 can serve as the operating power source for vehicle 1, for example, for the electrical system of vehicle 1, such as for the power requirements of vehicle 1's starting, navigation, and operation. In another embodiment of this application, the battery device 10 can not only serve as the operating power source for vehicle 1, but also as the driving power source for vehicle 1, replacing or partially replacing gasoline or natural gas to provide driving power for vehicle 1.
[0247] [Positive electrode plate]
[0248] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0249] In some embodiments, the positive electrode film layer further includes a binder. As an example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins.
[0250] In some embodiments, the positive electrode film layer further includes a conductive agent. As an example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0251] In one embodiment, the positive electrode sheet can be prepared by forming a positive electrode slurry using the components described above. For example, the positive electrode active material, conductive agent, binder, and any other components are dispersed in a solvent (e.g., N-methylpyrrolidone) to form the positive electrode slurry. The positive electrode slurry is then coated onto a positive electrode current collector, and after drying, cold pressing, and other processes, the positive electrode sheet is obtained.
[0252] [Negative electrode plate]
[0253] In some embodiments, the negative electrode current collector can be a metal foil or a composite negative electrode current collector. The negative electrode current collector can be a copper foil. The composite negative electrode current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0254] The negative electrode film layer includes a negative electrode active material. The negative electrode active material can be any negative electrode active material known in the art for use in batteries. As an example, in addition to silicon-based materials, the negative electrode active material can include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, tin-based materials, and lithium titanate, etc. The silicon-based material can be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.
[0255] The negative electrode film layer may also optionally include a binder. As an example, the binder may include one or more of the following: styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC), water-soluble unsaturated resin SR-1B, waterborne acrylic resins (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS).
[0256] The negative electrode film may optionally include a conductive agent. The conductive agent may be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0257] In one embodiment, the negative electrode sheet can be prepared by forming a negative electrode slurry using the components described above. For example, the negative electrode active material, conductive agent, binder, and any other components are dispersed in a solvent (e.g., deionized water) to form the negative electrode slurry. The negative electrode slurry is then coated onto a negative electrode current collector, and after drying, cold pressing, and other processes, the negative electrode sheet is obtained.
[0258] This application provides a battery device, including the battery cell in any of the above embodiments.
[0259] This application provides an electrical device including a battery cell or battery device as described in any of the above embodiments, wherein the battery cell or battery device is used to store or provide electrical energy.
[0260] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0261] [Example]
[0262] Example 1
[0263] (1) Preparation of positive electrode sheet
[0264] The positive electrode includes a positive current collector, a positive conductive layer on the positive current collector, and a positive film layer. The positive current collector is an aluminum foil with a thickness of 13 μm.
[0265] The positive electrode conductive layer on the positive electrode current collector is a film formed by uniformly mixing the positive electrode conductive agent superconducting carbon, the positive electrode binder polyvinylidene fluoride (PVDF), and the solvent N-methylpyrrolidone (NMP), coating it on the surface of the current collector, and drying it. The thickness is 1 μm. The positive electrode conductive layer contains 40% positive electrode conductive agent by mass and 60% positive electrode binder by mass.
[0266] The positive electrode film layer comprises a film layer formed by uniformly coating a positive electrode slurry (solvent being N-methylpyrrolidone, NMP) onto the surface of a positive electrode conductive layer, followed by drying and cold pressing. The positive electrode film layer comprises positive electrode active material, binder polyvinylidene fluoride (PVDF), and conductive agent acetylene black in a weight ratio of 97:2:1.
[0267] The positive electrode active material includes lithium iron phosphate (LFP), which has a coating layer covering the surface of the LFP particles. The coating layer includes lithium titanium iron phosphate (Li2FeTi(PO4)3) and carbon. Based on the total mass of the positive electrode active material, the carbon content is 1.12%. The powder compaction density of LFP at 30000N is 2.63 g / cm³. 3 The single-sided density of the positive electrode film is 330 mg / 1540.25 mm. 2 The compaction density of the positive electrode film at 100% SOC is 2.75 g / cm³. 3 .
[0268] (2) Preparation of negative electrode sheet
[0269] The negative electrode sheet includes a negative current collector, a negative conductive layer on the negative current collector, and a negative film layer. The negative current collector is a copper foil with a thickness of 6μm.
[0270] The negative electrode conductive layer on the negative electrode current collector is a film formed by uniformly mixing the negative electrode conductive agent superconducting carbon, the negative electrode binder styrene-butadiene rubber SBR, the thickener sodium carboxymethyl cellulose (CMC-Na), and the solvent water, coating it on the surface of the negative electrode current collector, and drying it. The thickness is 1μm. The negative electrode conductive agent has a mass content of 35% in the negative electrode conductive layer, the negative electrode binder has a mass content of 60% in the negative electrode conductive layer, and the thickener has a mass content of 5% in the negative electrode conductive layer.
[0271] The negative electrode film consists of a film formed by uniformly coating a negative electrode slurry (using deionized water as the solvent) onto the surface of a negative electrode conductive layer, followed by drying and cold pressing. The single-sided density of the negative electrode film is 130 mg / 1540.25 mm². 2 The compaction density of the negative electrode film at 100% SOC is 1.30 g / cm³. 3 .
[0272] The negative electrode film layer includes a first negative electrode film layer and a second negative electrode film layer. The second negative electrode film layer is located on the surface of the negative electrode conductive layer, and the first negative electrode film layer is located on the surface of the second negative electrode film layer. The first negative electrode film layer includes composite graphite particles, silicon-carbon composite particles, conductive agent acetylene black, binder styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose in a mass ratio of 92.5:5:0.5:1:1. The composite graphite particles in the first negative electrode film layer have a Dv50 of 11.5 μm. The second negative electrode film layer includes composite graphite particles, silicon-carbon composite particles, conductive agent acetylene black, binder styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose in a mass ratio of 91.5:5:0.5:2:1. The composite graphite particles in the second negative electrode film layer have a Dv50 of 14.4 μm. The thickness ratio of the first negative electrode film layer to the second negative electrode film layer is 5:5, the Dv50 of the silicon-carbon composite particles is 9.5μm, and the mass ratio of silicon element in the silicon-carbon composite particles to the negative electrode film layer is 2.3%.
[0273] (3) Separating membrane
[0274] The separator membrane includes a base membrane 80, two first functional layers 801, and a second functional layer 802 (the structure of the separator membrane in Example 1 can be found in [reference]). Figure 1 As shown, the first functional layer is disposed on both sides of the base film, and the second functional layer is disposed between the base film and the first functional layer facing the positive electrode.
[0275] The base film is a 5μm polyethylene film with a porosity of 35%, a pore size of 150nm, and a pore area to base film area ratio of 23%.
[0276] The first functional layer includes a first inorganic material and a fluoropolymer, wherein the first inorganic material is aluminum oxide and the fluoropolymer is PVDF; the second functional layer includes a second inorganic material, wherein the second inorganic material is aluminum oxide and the thickness of the second functional layer is 2 μm.
[0277] The air permeability of the separator is 150s, and the tensile strength of the separator in the length (MD) direction is 3200Kgf / cm. 2 The thermal shrinkage in the width (TD) direction at 150°C for 30 minutes is 1.0%.
[0278] (4) Electrolyte
[0279] The electrolyte comprises a solvent, consisting of 39.75% by mass of a chain carboxylic acid ester solvent (ethyl acetate) and 39.75% by mass of a carbonate solvent (27.8% by mass of ethylene carbonate EC and 11.95% by mass of dimethyl carbonate). The mass content of each component in the solvent is calculated based on the mass of the electrolyte.
[0280] The electrolyte includes electrolyte salts, which consist of lithium bis(fluorosulfonyl)imide (LiFSI) at a mass content of 4.5% and lithium hexafluorophosphate (LiPF6) at a mass content of 10.5%. The mass content of the lithium salts is calculated based on the mass of the electrolyte.
[0281] The electrolyte includes additives, and the total mass content of the additives is 5.5% based on the mass of the electrolyte. The additives include vinylene carbonate (VC), fluoroethylene carbonate (FEC), 1,3-propylene sulfonate lactone (PS), vinyl sulfite (DTD), and lithium difluorophosphate (LiPO2F2) in a mass ratio of 2.5:1:0.5:0.5:0.5.
[0282] (5) Preparation of battery cells
[0283] The positive electrode, separator, and negative electrode are stacked and wound in sequence to obtain a wound electrode assembly. The electrode assembly is then placed in a square aluminum shell, dried, and injected with electrolyte. After processes such as encapsulation, settling, formation, aging, secondary encapsulation, capacity testing, and shaping, a battery cell is obtained. The electrolyte injection volume per Ah of the battery cell is 2.5 g / Ah.
[0284] Examples 2-4
[0285] The difference between Examples 2-4 and Example 1 is that the air permeability of the separator is different.
[0286] It should be noted that the air permeability of the separator can be controlled by adjusting the porosity of the base membrane, and different porosities of the base membrane can correspond to different air permeabilities of the separator.
[0287] Examples 5-8
[0288] The difference between Examples 5-8 and Example 1 is that the density of one side of the negative electrode film is different.
[0289] Examples 9-11
[0290] The difference between Examples 9-11 and Example 1 is that the mass content of silicon element is different based on the total mass of the negative electrode film.
[0291] Examples 12-14
[0292] The difference between Examples 12-14 and Example 1 is that the thickness of the second functional layer is different.
[0293] It should be noted that the thickness of the second functional layer affects the air permeability of the separator.
[0294] Example 15
[0295] The difference between Example 15 and Example 1 lies in the structure of the separator. In Example 15, the separator includes two second functional layers (the structure of which can be found in [reference needed]). Figure 2 (As shown).
[0296] Example 16
[0297] The difference between Example 16 and Example 1 is that the first functional layer does not include the first inorganic material.
[0298] Comparative Example 1
[0299] The difference between Comparative Example 1 and Example 1 is that the air permeability of the separator is 223s. The pore size in the base film is 80nm, and the ratio of the pore area to the base film area is 17%.
[0300] Comparative Example 2
[0301] The difference between Comparative Example 2 and Example 1 is that the air permeability of the separator is 67s. The pore size in the base film is 500nm, and the ratio of the pore area to the base film area is 43%.
[0302] Comparative Example 3
[0303] The difference between Comparative Example 3 and Example 1 is that the single-sided density of the negative electrode film layer is less than 100 mg / 1540.25 mm. 2 .
[0304] Comparative Example 4
[0305] The difference between Comparative Example 4 and Example 1 is that the single-sided density of the negative electrode film layer is greater than 200 mg / 1540.25 mm. 2 .
[0306] Table 1 Test data for the examples and comparative examples
[0307]
[0308]
[0309] Table 2 Test data for some embodiments
[0310]
[0311] Table 3 Test data for some embodiments
[0312]
[0313] In the embodiment data section of this application, the reliability of a single battery cell is demonstrated by conducting an overcharge experiment on the cell and observing whether thermal runaway occurs after overcharging. After overcharging, lithium dendrites appear within the cell. The permeability of the separator plays a crucial role in preventing the dendrites from piercing the separator. Dendrite piercing the separator can easily lead to a short circuit between the positive and negative electrodes, thereby triggering thermal runaway. The fast-charging performance of the battery cell is demonstrated by the charging time, and the energy density of the battery cell is demonstrated by its volumetric energy density.
[0314] In conjunction with Examples 1-16 and Comparative Examples 1-4, in a battery cell comprising silicon-based materials, the air permeability of the separator is set to be 75s to 210s, and the one-sided density of the negative electrode film layer is 100mg / 1540.25mm². 2 Up to 200mg / 1540.25mm 2 The battery cells have high energy density while also achieving good fast charging performance and high reliability.
[0315] Referring to Examples 1-4 and 12-16, setting the air permeability of the separator to 75s to 210s results in good fast-charging performance and high reliability for the battery cell; setting the air permeability of the separator to 132s to 180s further improves the fast-charging performance of the battery cell. Referring to Examples 1 and 16, including a first inorganic material in the first functional layer facilitates lithium-ion transport, thereby improving the fast-charging performance of the battery cell.
[0316] As shown in Examples 1-4, by setting the porosity of the base film to 30% to 60%, the separator has suitable porosity and air permeability, which is conducive to electrolyte wetting of the separator and the battery cell has good fast charging performance; by setting the porosity of the base film to 35% to 45%, the battery cell has good fast charging performance while also having high tensile strength.
[0317] Combining Examples 1 and 5-8, the single-sided density of the negative electrode film is 100 mg / 1540.25 mm². 2 Up to 200mg / 1540.25mm 2 The battery cells have high energy density while also having good fast charging performance.
[0318] In conjunction with Examples 1 and 9-11, when the mass content of silicon is 0.3% to 10%, the battery cell achieves both high energy density and good fast charging performance.
[0319] Referring to Examples 1 and 12-14, by setting the thickness of the second functional layer to 0.5 μm to 3 μm, the separator exhibits suitable air permeability and porosity, resulting in good fast-charging performance of the battery cell. By setting the coating thickness of the second functional layer to 0.75 μm to 2 μm, the separator exhibits even more suitable air permeability and porosity, resulting in good fast-charging performance of the battery cell, while also possessing high energy density. When the thickness of the second functional layer is greater than or equal to 0.5 μm, the separator is not punctured, and it also exhibits high tensile strength and low thermal shrinkage, resulting in high reliability of the battery cell.
[0320] As shown in Examples 1 and 15, setting two second functional layers on both sides of the base film is beneficial to improving the tensile strength of the separator and reducing the thermal shrinkage of the separator.
[0321] It should be noted that this application is not limited to the above embodiments. The above embodiments are merely examples, and embodiments that have the same structure and achieve the same effect as the technical concept within the scope of this application are all included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
[0322] The following is a brief description of the testing methods for the physicochemical and performance parameters involved in the embodiments of this application. It should be understood that the following testing methods are only examples, and other testing methods known in the art can also be used for testing.
[0323] 1. Charging time test method
[0324] Fast-charging performance was tested on battery cells fabricated as stacked three-electrode units. As one example, an electrode assembly was prepared by stacking the positive electrode, separator, third electrode (copper wire), separator, and negative electrode in that order. The electrode assembly was then placed in a housing, and the prepared electrolyte was added. After encapsulation, settling, formation, and aging processes, a battery cell was obtained. As another example, the battery cell was disassembled to obtain the positive electrode, negative electrode, and separator. The positive electrode, negative electrode, and separator were immersed in DMC solvent for at least 72 hours to allow the electrolyte solvent, lithium salt, and additives to be completely leached out. The positive and negative electrodes were then dried in a vacuum oven to prepare a three-electrode battery cell.
[0325] The battery was charged at different states of charge (SOC) with tests conducted every 5% SOC. The maximum charging current was measured and recorded at 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, and 80% SOC. The time taken to charge from 10% SOC to 80% SOC at the maximum charging current was also recorded. This time was used to measure the fast charging performance of the individual battery cells.
[0326] The maximum charging current corresponding to different SOCs can be obtained as follows: At 25°C, select different current densities to charge the battery cells, and record the SOC when the third electrode potential reaches 0mV under that current. Then, the current corresponds to the maximum charging current of that SOC.
[0327] 2. Energy density testing
[0328] At 25℃, the battery cell was discharged at a constant current of 0.33C to 2.0V, left to stand for 30 minutes, charged at a constant current of 0.33C to the upper limit cutoff voltage of 3.8V, and then charged at a constant voltage to a current of 0.05C, left to stand for 30 minutes; discharged at a constant current of 0.33C to the cutoff voltage of 2.0V, and the discharge capacity at this time was recorded, and the discharge energy E0 was obtained.
[0329] Volumetric energy density (Wh / L) = Discharge energy E0 / Volume of a single battery cell (L).
[0330] The volume of a single battery cell is the product of its dimensions along its length, width, and height.
[0331] 3. Test of air permeability of the separator membrane
[0332] After disassembling the battery cell, the separator is obtained. The separator at the corner of the wound structure is taken as a test sample, and then it can be tested using an air-permeability tester (e.g., a Gurley air permeability tester with an air volume of 100cc) in accordance with GB / T 458-2008.
[0333] As an example, the dried release film was cut into 6.45cm pieces. 2 The size was measured by testing 100 mL of air passing through 6.45 cm under a pressure of 1.21 kPa. 2 The time taken for the isolation membrane to be in place is used as the air permeability of the isolation membrane.
[0334] 4. Porosity testing
[0335] After disassembling the battery cell, a separator is obtained. The coating on the separator is scraped off to obtain the base film, and then the porosity of the base film is tested.
[0336] As an example, the true density of the base film was measured using the Archimedes method, the weight of the base film was determined using an electronic balance, the thickness of the base film was measured using a micrometer, and the length and width of the base film were measured using a ruler to calculate the volume of the base film. The porosity of the base film = 1 - weight of the base film / (volume of the base film × true density of the base film).
[0337] As an example, the specific procedure for testing the true density of a base film using the Archimedes method is as follows: Weigh the dry base film on a balance to determine its mass in air; immerse the base film in a liquid, ensuring complete submersion and no air bubbles, and record its mass in the liquid; measure the density of the liquid using a standard hydrometer, and then calculate the true density of the base film. The true density of the base film is calculated as follows: True density of the base film = [Mass of the base film in air / (Mass of the base film in air - Mass of the base film in the liquid)] × Density of the liquid.
[0338] 5. Testing the areal density of the base film
[0339] As an example, after disassembling the battery cell, a separator is obtained. The coating on the separator is scraped off to obtain the base film. Then, the mass of the base film is measured using Archimedes' method, and the length and width of the base film are measured using a ruler, thereby calculating the area of the base film. The areal density of the base film = mass of the base film / area of the base film.
[0340] 6. Tensile strength test of the separator membrane
[0341] After disassembling the battery cell, the separator is obtained. Then, the tensile strength of the separator is tested with a tensile tester in accordance with GB / T1040[1].3-2006.
[0342] As an example, the separator is cut into a rectangular sample. Along the length of the separator, both ends of the separator are fixed to the clamps at both ends of the tensile tester. Then, the clamps of the tensile tester move at a speed of 50 mm / min. The tensile force displayed by the tensile tester when the separator breaks is tested. Tensile strength = tensile force / area of separator, where the area of separator is the product of the thickness and length of separator.
[0343] 7. Test of heat shrinkage of the release film
[0344] After disassembling the battery cells, the separator is obtained, and then the heat shrinkage of the separator is tested in accordance with GB / T 36363-2018.
[0345] As an example, the initial length of the release liner is measured using a ruler. The release liner (e.g., 100mm long, 50mm wide) is then placed in a forced-air drying oven and heated at a constant temperature of 150°C for 30 minutes. The length of the release liner after heating is then measured. Shrinkage rate = 1 - length of the release liner after heating / initial length of the release liner.
[0346] 8. Test of the mass content of electrolyte salts
[0347] The concentration of inorganic components / lithium salts in the electrolyte can be qualitatively or quantitatively analyzed using ion chromatography, referring to standard JY / T020-1996 "General Rules for Ion Chromatography Analysis". In the embodiments of this application, freshly prepared electrolyte can be used as a sample, or the free electrolyte from a fresh battery can be used as a sample. Alternatively, a fully discharged battery (discharged to the lower cutoff voltage so that the battery's state of charge is approximately 0% SOC) can be disassembled in reverse, and the free electrolyte obtained from the battery can be used as a sample for detection using ion chromatography.
[0348] 9. Test methods for areal density and compacted density
[0349] Take a single-sided coated negative electrode sheet (if it is a double-sided coated electrode sheet, the negative electrode film layer on one side can be wiped off first), cut it into a small circular sheet with an area of S1, weigh it and record its weight as M1, and measure its thickness H1. Then wipe off the negative electrode film layer of the weighed negative electrode sheet, weigh the negative electrode current collector and record it as M0, and measure its thickness H0. The single-sided density of the negative electrode film layer = (weight of negative electrode sheet M1 - weight of negative electrode current collector M0) / S1, and the compaction density PD of the negative electrode film layer = surface density of negative electrode film layer / (electrode sheet thickness - current collector thickness).
[0350] The areal density and compaction density of the positive electrode film can be tested using the same method described above.
[0351] 10. High Voltage Breakdown Test
[0352] The positive electrode, separator, and negative electrode are assembled into an aluminum shell, dried, and then sealed into a dry cell without electrolyte. A clamping force of 0.3 MPa is applied to the large surface area (the surface with the largest surface area) on both sides of the cell. The voltage is applied to the positive and negative electrodes of the dry cell from 0V to the set value of 100V and held for 10s. After completion, the voltage is cut off and the resistance of the positive and negative electrodes is tested immediately. If the test resistance is less than 1MΩ, it is considered that the separator has been partially broken down by voltage.
[0353] 11. Overcharge thermal runaway test
[0354] The battery cell assembly fixture is specifically designed so that the battery is placed in the test fixture (fixture-battery-fixture). The fixture covers the large surface of the battery, and the fixture surface is insulated with Teflon. The fixture force is 3000N. The upper surface of the fixture is flush with the top cover of the battery, and the bottom of the battery is suspended. Then, a full charge is performed: charge at 1 / 3C current to the upper limit voltage (e.g., 3.8V), then charge at constant voltage to 0.05C, let it rest for 30 minutes, and then perform an overcharge test: charge at 1 / 3C current for 30 minutes. If fire or explosion occurs, it is considered as thermal runaway.
Claims
1. A battery cell, characterized in that, include: A positive electrode sheet, the positive electrode sheet comprising a positive current collector and a positive electrode film layer disposed on at least one side surface of the positive current collector, the positive electrode film layer comprising a positive electrode active material, the positive electrode active material comprising a lithium phosphate; A negative electrode sheet, comprising a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer comprising a negative electrode active material, the negative electrode active material comprising a silicon-based material, and the one-sided density of the negative electrode film layer being 100 mg / 1540.25 mm². 2 Up to 200mg / 1540.25mm 2 ; A separator membrane is disposed between the positive electrode and the negative electrode. The air permeability G of the separator membrane satisfies: 75s ≤ G ≤ 210s, wherein the air permeability is defined as 100 mL of air passing through 6.45 cm under a pressure of 1.21 kPa. 2 The time taken for the isolation membrane to be in place.
2. The battery cell according to claim 1, characterized in that, 132s≤G≤180s.
3. The battery cell according to claim 1 or 2, characterized in that, Based on the total mass of the negative electrode film, the silicon content in the silicon-based material is from 0.3 wt% to 10 wt%.
4. The battery cell according to any one of claims 1-3, characterized in that, The single-sided density of the negative electrode film is 100 mg / 1540.25 mm. 2 Up to 180mg / 1540.25mm 2 .
5. The battery cell according to any one of claims 1-4, characterized in that, The isolation membrane includes a base membrane and coatings disposed on both sides of the base membrane, wherein the porosity of the base membrane is 30% to 60%.
6. The battery cell according to claim 5, characterized in that, The porosity of the base membrane is 35% to 45%.
7. The battery cell according to claim 5 or 6, characterized in that, The base film includes pores, and the pores satisfy at least one of the following conditions: The average pore diameter is 10 nm to 400 nm; The ratio of the area of the pore to the area of the base film is 10% to 50%.
8. The battery cell according to claim 7, characterized in that, The hole satisfies at least one of the following conditions: The average pore diameter is 40 nm to 160 nm; The ratio of the area of the pore to the area of the base film is 15% to 30%.
9. The battery cell according to any one of claims 5-8, characterized in that, The base film satisfies at least one of the following conditions: The thickness of the base film is 3.5 μm to 7 μm; The areal density of the base film is 2 g / m³. 2 Up to 5g / m 2 .
10. The battery cell according to any one of claims 5-9, characterized in that, The coating includes two first functional layers and at least one second functional layer. The first functional layers are disposed on both sides of the base film, and the second functional layer is disposed between the base film and the first functional layer. The first functional layer comprises a first inorganic material and a fluoropolymer, and the second functional layer comprises a second inorganic material.
11. The battery cell according to claim 10, characterized in that, The coating comprises two first functional layers and one second functional layer, wherein the second functional layer is disposed between the base film and the first functional layer facing the positive electrode sheet, or the second functional layer is disposed between the base film and the first functional layer facing the negative electrode sheet.
12. The battery cell according to claim 10, characterized in that, The coating comprises two first functional layers and two second functional layers, wherein the second functional layers are disposed between the base film and the first functional layers.
13. The battery cell according to any one of claims 10-12, characterized in that, The thickness of the second functional layer is 0.5 μm to 3 μm.
14. The battery cell according to claim 13, characterized in that, The thickness of the second functional layer is 0.75 μm to 2 μm.
15. The battery cell according to any one of claims 10-14, characterized in that, The first inorganic substance includes one or more of silicon oxide, aluminum oxide, boehmite, barium sulfate, calcium fluoride, calcium oxide, titanium oxide, zinc oxide, magnesium oxide, zirconium oxide, and tin oxide; and / or, The second inorganic substance includes one or more of silicon oxide, aluminum oxide, boehmite, barium sulfate, calcium fluoride, calcium oxide, titanium oxide, zinc oxide, magnesium oxide, zirconium oxide, and tin oxide.
16. The battery cell according to any one of claims 10-15, characterized in that, The fluoropolymer includes polyvinylidene fluoride.
17. The battery cell according to any one of claims 1-16, characterized in that, Along the width direction of the separator, the amount of heat shrinkage T of the separator at 150°C for 30 minutes satisfies: T≤3%.
18. The battery cell according to claim 17, characterized in that, 0.1%≤T≤2%。 19. The battery cell according to any one of claims 1-18, characterized in that, Along the length of the separator, the tensile strength G of the separator satisfies: 2700 kgf / cm 2 ≤G≤6000Kgf / cm 2 .
20. The battery cell according to any one of claims 1-19, characterized in that, The negative electrode film layer includes a first negative electrode sub-film layer and a second negative electrode film layer, wherein the first negative electrode film layer is farther away from the negative electrode current collector relative to the second negative electrode film layer.
21. The battery cell according to claim 20, characterized in that, The first negative electrode film layer includes the silicon-based material and composite graphite, and the second negative electrode film layer includes at least one of composite graphite and natural graphite, and the silicon-based material.
22. The battery cell according to claim 21, characterized in that, The composite graphite includes a body and a coating layer disposed on at least a portion of the surface of the body, the body comprising artificial graphite and the coating layer comprising amorphous carbon.
23. The battery cell according to claim 22, characterized in that, The body comprises multiple primary particles of artificial graphite.
24. The battery cell according to claim 22 or 23, characterized in that, Based on the total mass of the composite graphite, the mass content of amorphous carbon in the coating layer is 2 wt% to 5 wt%.
25. The battery cell according to any one of claims 20-24, characterized in that, The volume average particle size of the negative electrode active material in the first negative electrode film layer is 7.5 μm to 18.5 μm, and the volume average particle size of the negative electrode active material in the second negative electrode film layer is 10.5 μm to 19.5 μm.
26. The battery cell according to any one of claims 20-25, characterized in that, The thickness ratio of the first negative electrode film layer to the second negative electrode film layer is 2:8 to 8:
2.
27. The battery cell according to claim 26, characterized in that, The thickness ratio of the first negative electrode film layer to the second negative electrode film layer is 4:6 to 5:
5.
28. The battery cell according to any one of claims 1-27, characterized in that, The negative electrode sheet includes a negative electrode conductive layer, which is disposed between the negative electrode current collector and the negative electrode film layer, and the negative electrode conductive layer includes a conductive agent.
29. The battery cell according to claim 28, characterized in that, The thickness of the negative electrode conductive layer is 0.5 μm to 2 μm.
30. The battery cell according to any one of claims 1-29, characterized in that, The lithium-containing phosphate includes a lithium-containing phosphate matrix and a coating layer, the coating layer being located on at least a portion of the surface of the lithium-containing phosphate matrix, and the coating layer containing carbon.
31. The battery cell according to claim 30, characterized in that, Based on the total mass of the lithium phosphate, the carbon content is between 0.8% and 2.3%.
32. The battery cell according to any one of claims 1-31, characterized in that, The positive electrode sheet further includes a positive conductive layer, which is disposed between the positive current collector and the positive film layer, and the positive conductive layer includes a conductive agent.
33. The battery cell according to claim 32, characterized in that, The thickness of the positive electrode conductive layer is 0.5 μm to 2 μm.
34. The battery cell according to any one of claims 1-33, characterized in that, The battery cell includes an electrolyte, which includes a carboxylic acid ester solvent.
35. The battery cell according to claim 34, characterized in that, The carboxylic acid ester solvents include one or more of methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, methyl butyrate, and ethyl butyrate.
36. The battery cell according to any one of claims 1-35, characterized in that, The battery cell includes an electrolyte, which includes an electrolyte salt, including lithium difluorosulfonylimide and lithium hexafluorophosphate.
37. The battery cell according to claim 36, characterized in that, The molar concentration of lithium bis(fluorosulfonyl)imide in the electrolyte is from 0.2 mol / L to 0.5 mol / L.
38. The battery cell according to any one of claims 1-37, characterized in that, The battery cell includes an electrolyte, which includes additives, including at least one of vinylene carbonate, fluoroethylene carbonate, 1,3-propylene sulfonate lactone, vinyl sulfite, and lithium difluorophosphate.
39. The battery cell according to any one of claims 1-38, characterized in that, The electrolyte injection volume in the battery cell is from 2.2 g / Ah to 2.8 g / Ah.
40. The battery cell according to any one of claims 1-39, characterized in that, The volumetric energy density of the battery cell is 440Wh / L to 550Wh / L, and the charging time of the battery cell from 10% SOC to 80% SOC is 7min to 20min.
41. A battery device, characterized in that, include: Multiple battery cells according to any one of claims 1-40.
42. An electrical appliance, characterized in that, include: A plurality of battery cells according to any one of claims 1-40, or a battery device according to claim 41, wherein the battery cells or battery device are used to store or provide electrical energy.
